Hybride Beamformingsysteme niedriger Komplexität für den Mobilfunk - Eisenbeis, Joerg Andreas (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2022)
An important method to increase the spectral efficiency of wireless radio communication networks is the use of multiple-input multiple-output communication systems operating in the centimetre and millimetre wave region. How these multiple-input multiple-output communication systems can be realised with as little hardware effort as possible using hybrid beamforming architectures is the subject of this work.